Mengkaji Sistem Keuangan Berbasis Teknologi Blockchain dalam Ekonomi Moneter Islam - Muhammad Syahrul Hidayat; Agus Eko Sujianto; Binti Nur Asiyah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
Abstract. This research examines the Blockchain-based financial system in Islamic monetary economics. Through a literature review, this study finds that blockchain technology can support Shariah principles by regulating transactions in accordance with Islamic rules and enhancing financial transparency. Furthermore, blockchain technology can enhance financial security through encryption and strict access controls. The implementation of this technology also has the potential to improve financial inclusion by providing secure and efficient financial services to previously unbanked individuals. The findings of this research provide valuable insights for policymakers and practitioners in developing innovative solutions that strengthen the fair, transparent, and inclusive Islamic financial sector in the digital era.